Locating the Position of Environmental Education in the South African School Curriculum: The Case of Grade R - Hebe, Headman (Eurasia Journal of Mathematics, Science and Technology Education, 2019)
The South African Curriculum and Assessment Policy Statement (CAPS) advocates for the integration of Environmental Education (EE) in all grades and subjects. The purpose of this study was to conduct a review of CAPS documents that guide pedagogy in all three subjects offered in Grade R, namely; English (Home Language), Life Skills and Mathematics. This was done to determine whether an alignment exists between the South African school curriculum aims and the curriculum content to enable the implementation of EE as espoused in CAPS. Informed by literature, the researcher singles out the “failure” of the CAPS documents to pinpoint the topics that could be used to facilitate the implementation of EE to focus his investigation. He uses an interpretivist qualitative approach to direct this inquiry. Through the application of content analysis and the deductive, inductive and abductive modes of inference, he examines the CAPS documents used to guide pedagogy in Grade R to identify the topics that could be used to facilitate the implementation of EE. The findings suggest that the CAPS documents contain various topics that could enable the implementation of EE. These findings hold positive implications for the teaching of EE both in South Africa and elsewhere, globally.